Enhanced Silver Nanoparticle Synthesis by Escherichia Coli Transformed with Candida Albicans Metallothionein Gene - Yuan, Qunying (Materials (Basel), 2019)
In this study, the metallothionein gene of Candida albicans (C. albicans) was assembled by polymerase chain reaction (PCR), inserted into pUC19 vector, and further transformed into Escherichia coli (E. coli) DH5α cells. The capacity of these recombinant E. coli DH5α cells to synthesize silver nanoparticles was examined. Our results demonstrated that the expression of C. albicans metallothionein in E. coli promoted the bacterial tolerance to metal ions and increased yield of silver nanoparticle synthesis. The compositional and morphological analysis of the silver nanoparticles revealed that silver nanoparticles synthesized by the engineered E. coli cells are around 20 nm in size, and spherical in shape. Importantly, the silver nanoparticles produced by the engineered cells were more homogeneous in shape and size than those produced by bacteria lack of the C. albicans metallothionein. Our study provided preliminary information for further development of the engineered E. coli as a platform for large-scale production of uniform nanoparticles for various applications in nanotechnology.